The Genome Sequence of Taurine Cattle: A Window to Ruminant Biology and Evolution - Elsik, Christine G.; Tellam, Ross L.; Worley, Kim C.; Gibbs, Richard A.; Abatepaulo, Antonio R. R.; Abbey, Colette A.; Adelson, David L.; Aerts, Jan; Ahola, Virpi; Alexander, Lee; Alioto, Tyler; Snelling, Warren M.; et al. (Amer Assoc Advancement Science, 2009)
To understand the biology and evolution of ruminants, the cattle genome was sequenced to about sevenfold coverage. The cattle genome contains a minimum of 22,000 genes, with a core set of 14,345 orthologs shared among seven mammalian species of which 1217 are absent or undetected in noneutherian (marsupial or monotreme) genomes. Cattle-specific evolutionary breakpoint regions in chromosomes have a higher density of segmental duplications, enrichment of repetitive elements, and species-specific variations in genes associated with lactation and immune responsiveness. Genes involved in metabolism are generally highly conserved, although five metabolic genes are deleted or extensively diverged from their human orthologs. The cattle genome sequence thus provides a resource for understanding mammalian evolution and accelerating livestock genetic improvement for milk and meat production.